On the Move : The Politics of Social Change in Latin America - Veltmeyer, Henry (Book collections on Project MUSE., 2007)
Will social change in Latin America lead to a kinder, gentler form of globalization or a model that offers a radical rethinking of how we produce and distribute wealth? What are the effects on social movements and their ability to push for change when progressive governments are elected? Does democratic participation mean greater economic equality? On the Move addresses these questions by providing an up-to-date, continent-wide account of political and social change in Latin America. Globalization has, over the last two decades, structurally adjusted local communities to conform to a new world order. It is no surprise then that social discontent is widespread in those countries where large portions of the population have not shared in the gains of economic development. Nowhere is this more evident than in Latin America where social discontent has totally transformed the political landscape in recent years. Whether it is local communities writing their own budgets in Brazil, landless workers organizing in the fields of Bolivia or a new leftist government taking hold in Ecuador, change has been dramatic. The question now is whether this change will lead to a milder form of neo-liberal globalization, or whether these social movements will continue to push for a development alternative that aims not just for greater political participation but greater economic equality as well. Veltmeyer explores these forces of political change offering a critical analysis of the most recent research by political and economic sociologists, development economists, and political scientists.